Analisis dan Perancangan Sales Monitoring System Menggunakan Metode Rapid Application Development - Nurmiati, Evy; Azizah, Hafidh; Kamil, Musthafa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
In this competitive digital era, companies are required to have information systems that can support quick and accurate decision making. PT. ABC is one of the companies facing several challenges in managing sales division activities, which are still carried out manually using spreadsheets. This causes difficulties in monitoring sales performance in real time, increases the risk of data duplication, and reduces the effectiveness of strategic decision making. This study aims to analyze and design a web-based sales monitoring system to support the company's strategic decision-making. The research method used is Rapid Application Development (RAD) with data collection methods including observation, interviews, and literature review, as well as PIECES analysis to evaluate the weaknesses of the current system, and the MoSCoW method to prioritize system features. The results of this research include a system design comprising an interactive dashboard, sales activity recording, team structure management, target setting, and structured reporting. The system is designed using the UML modeling language, which includes use cases, activity diagrams, sequence diagrams, and class diagrams, as well as a user interface prototype.